Development and validation of entrustable professional activity (EPA) encompassing examiner competencies in the Malaysian anaesthesiology programme - Hashim, Noorjahan Haneem Md (2021)
Examiner training is essential to ensure the trustworthiness of the examination process and results. This study aims to develop and validate the Malaysian Primary Anaesthesiology examiner's core entrustable professional activities (EPA) to facilitate examiner training. We describe the novel concept of using the entrustable professional activities (EPA) framework for examiners. In a three-staged (problem identification and general needs assessment, EPA development and EPA validation) mixed-method study, examiner training needs, essential examiner tasks and competencies required to perform them were identified through triangulation of information from document review, focus group discussions and three rounds of Delphi questionnaires. These tasks were then described in the EPA framework and were validated by a panel of experts. Seven EPAs were identified as essential and were described using the EPA framework. These EPAs were: constructing questions with answer key and rating rubrics according to guidelines, vetting examination questions, rating candidates’ performance, conducting a viva examination, constructive participation in decision-making meetings, writing an examiner report and giving feedback regarding candidates’ performance to respective universities. The competencies required to perform them are classified as task-related and professional competencies. Task-related competencies consist of subject matter expertise, examination technique, medical education knowledge, knowledge of the examination system and process, communication and teamwork. Professional competencies include agency, reliability, integrity, humility and benevolence. Activities that would support examiner entrustment and credentialing include active clinical practice, attending task-specific examiner training, and observing the examination process. All seven EPAs met our criteria for scale-level content validity index acceptance of 0.80. Our findings confirmed the need for examiner training for the Malaysian Anaesthesiology Primary examination. We identified and described seven EPAs performed by Primary Anaesthesiology examiners, with their essential competencies and features. This information can be used for examiner recruitment and training by the Malaysian Anaesthesiology Specialty Conjoint Board to the quality of the Primary examination.